MANAJEMEN LABA PADA PERUSAHAAN DENGAN PERMASALAHAN FREE CASH FLOW DAN PERAN MODERASI DARI MONITORING EKSTERNAL - Tresnaningsih, Elok (UI Scholars Hub, 2008)
This study examines whether low-growth companies with free cash flow (HFLG) will use income-increasing discretionary accruals to offset the low or negative earnings that inevitably accompany investment with negative net presents values (NPVs). Using 413 manufacturing company year observations over the period 2001-2005, the results show that there is a significantly association between HFLG and increasing discretionary accruals. This study also examines the role o f monitoring by auditors, creditors, and independent commissioners in mitigating the relation o f HFLG and income-increasing discretionary accruals. The results show that (1) monitoring by high-quality auditors and high-proportion o f independent commisioners are effective in mitigating the association o f HFLG and income- increasing discretionary accruals, which suggest that both their monitoring are more pronounced fo r HFLG firm s and (2) monitoring by high-debt creditors are effective in reducing income-increasing discretionary accruals, but their monitoring are not found to be more pronounced in HFLG firm. This result suggests that the vigilance o f creditors are more likely to increase when debt increase.